High-Resolution Comparative Genomics of Salmonella Kentucky Aids Source Tracing and Detection of ST198 and ST152 Lineage-Specific Mutations - Soltys, Rachel C.; Sakomoto, Carson K.; Oltean, Hanna N.; Guard, Jean; Haley, Bradd J.; Shah, Devendra H. (Frontiers in Sustainable Food Systems, 2021)
Nontyphoidal Salmonella (NTS) is a major cause of foodborne illness globally. Salmonella Kentucky is a polyphyletic NTS serovar comprised of two predominant sequence types (STs): ST152 and ST198. Epidemiological studies have revealed that ST152 is most prevalent in US poultry whereas ST198 is more prevalent internationally. Interestingly, ST152 is sporadically associated with human illness, whereas ST198 is more commonly associated with human disease. In this study, we compared the antimicrobial resistance phenotypes and genetic relationship using sub-genomic fingerprinting of 26 clinical strains of S. Kentucky isolated in Washington State between 2004 and 2014, and 140 poultry-associated strains of S. Kentucky mostly recovered from the northwestern US between 2004 and 2014. We sequenced whole genomes of 2 fluoroquinolone-susceptible (FluS) and 4 fluoroquinolone-resistant (FluR) ST198 human clinical isolates along with ST152 strains from humans (n=4) and poultry (n=4) from the northwestern US. Genome sequences of these isolates were compared with a global database of S. Kentucky genomes representing 400 ST198 and 50 ST152 strains. The results of the phenotypic, genotypic, and case report data on food consumption and travel show that human infections caused by FluR S. Kentucky ST198 in WA State originated from outside of North America. In contrast, FluS S. Kentucky ST198 and S. Kentucky ST152 infection have a likely domestic origin, with domestic cattle and poultry being the potential sources. We also identified a small number of lineage-specific non-synonymous single nucleotide polymorphisms (SNPs) that distinguish ST198 and ST152. These SNPs may provide good targets for further investigations on variation in virulence, metabolic adaptation to different environments, and potential for the development of intervention strategies to improve the safety of food.